Chromosomal aberrations involving telomeres and interstitial telomeric sequences - Bolzán, Alejandro Daniel (2012)
Telomeres are specialised nucleoproteic complexes localised at the physical ends of linear eukaryotic chromosomes that maintain their stability and integrity. In vertebrate chromosomes, the DNA component of telomeres is constituted by (TTAGGG)n repeats, which can be localised at the terminal regions of chromosomes (true telomeres) or at intrachromosomal sites (interstitial telomeric sequences or ITSs, located at the centromeric region or between the centromere and the telomere). In the past two decades, the use of molecular cytogenetic techniques has led to a new spectrum of spontaneous and clastogen-induced chromosomal aberrations being identified, involving telomeres and ITSs. Some aberrations involve the chromosome ends and, indirectly, the telomeric repeats located at the terminal regions of chromosomes (true telomeres). A second type of aberrations directly involves the telomeric sequences located at the chromosome ends. Finally, there is a third class of aberrations that specifically involves the ITSs. The aims of this review are to provide a detailed description of these aberrations and to summarise the available data regarding their induction by physical and chemical mutagens.